Novel Strategy for the Construction of Genomic Mutants of the Antarctic Bacterium Pseudoalteromonas haloplanktis TAC125. - GIULIANI, MARIA; PARRILLI, ERMENEGILDA; PEZZELLA, Cinzia; RIPPA, VALENTINA; DUILIO, ANGELA; MARINO, GENNARO; TUTINO, MARIA LUISA (Argelia Lorence, 2012)
The sequencing and the annotation of the marine Antarctic Pseudoalteromonas haloplanktis TAC125 genome has paved the way to investigate on the molecular mechanisms involved in adaptation to cold conditions. The growing interest in this unique bacterium prompted the developing of several genetic tools for studying it at the molecular level. To allow a deeper understanding of the PhTAC125 physiology a genetic system for the reverse genetics in this bacterium was developed. In the present work, we describe a practical technique for allelic exchange and/or gene inactivation by in-frame deletion and the use of a counterselectable marker in P. haloplanktis. The construction of suitable non-replicating plasmid and methods used to carry out a two-step integration-segregation strategy in this bacterium are reported in detail.Furthermore two examples, in which the developed methodology was applied to find out gene function or to construct genetically engineered bacterial strains, were described.